INVESTIGATION OF CHARACTERS VALUE IN THE ANIMATED FILM UP AND THEIR RELEVANCE TO THE CHARACTER EDUCATION OF PRIMARY SCHOOL STUDENTS - Kurniati, Anggun; Maisarah, Ira (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
The aim of this research is to analyze and describe the moral values in the film Up. This kind of study is qualitative research conducted in libraries. According to the findings, there are eight different types of character values: being gregarious or outgoing, accountable, inquisitive, creative, honest, considerate of others, and recognizing accomplishment. Students in elementary school can learn about this character value through character education. The main purpose to (1) describe the form of character values contained in the animated film Up. (2) determine the relevance of the character values contained in the animated film Up in relation to the character education of elementary school students.